Keeping the Tension: Pressures to Keep the Controversy in the Management Discipline - Fabian, Frances (Academy of Management Review, 2000)
Management journals often contain heated discussions about disciplinary approaches, or how and whether to legitimate different kinds of research. The author classifies nine such approaches in a typology. These varied approaches arise because none can fully accommodate the conflicting scientific and pragmatic pressures placed on academic research. The airing of these views, however, helps members of the discipline meet their responsibility to re-evaluate the value of existing research and new currents in an ongoing fashion.